Validation of antibacterial activity of Saponin against diarreagenic E.coli isolated from leaves and bark of Acacia arabica - Biswas, Deboshree; Roymon, M G (Journal of Phytology, 2012)
The leaf and bark extract of Acacia arabica constitute large amount of saponin (sapogenin aglycon) along with other polyphenolic compounds. The isolated sapogenin aglycon was tested against E.coli O22 associated with diarrheal infections in domesticated animals along with E.coli MTCC 723 strain. Both well-diffusion and broth micro dilution technique was used to detect antibacterial activity. Synergistic interaction was observed on combined administration of saponin with Chloramphenicol to inhibit tested organism.